METHOD OF INVESTIGATION OF VALIDITY OF TEST TASKS - Шибицька H. M. (Proceedings of National Aviation University (archive), 2021)
A study of methods for determining the reliability of test control, taking into account different assessment methods. The concept of validity is considered, which determines the reliability of the method of pedagogical measurements, which is important during the organization of test control of knowledge. The research results are substantiated by the practical use of the method.